AB0424 Il-6 receptor blockade induced a different immune response in rheumatoid arthritis patients with and without remission. (12th June 2018) - Diaz-Torne, C.; Estrada, P.; Ortiz, M.A.; Moya, P.; Moragues, C.; de la Fuente, D.; Torrente, V.; Ramirez, J.; Reina, D.; Moreno, M.; Casado, E.; Busquets, N.; et al.
Abstract : Background: Tocilizumab (TCZ) is a humanised antibody that blocks IL-6 receptor. Despite its effectiveness in rheumatoid arthritis (RA), there are patients that do not respond to the IL-6R blockade. The immune characteristics that would explain this lack of response are not known. Objectives: Our aim was to determine the tocilizumab-induced changes in CD4 +T cells of patients that achieve, or not, remission at 12 m. Methods: Prospective, multicenter study in 47 RA patients treated with TCZ during one year following standard clinical practice. Demographic, disease and treatment characteristics were collected at each visit. Ultrasound (US) grey scale and power doppler were assessed for joints and tendons using a semiquantitative scale from 0–3 points. Phenotyping of T lymphocytes was determined by flow cytometry and the plasma cytokine concentration was quantified by ELISA. Results: Forty seven patients were treated with a mean age of 54±11 y and 85% were women. Years of disease were 13±8. We segregated patients according to the DAS28-remission. 44% achieved remission at month 12. We observed that absolute counts of neutrophils and CD4 +T lymphocytes decreased significantly in the remission group but not in the other one. Both memory and naïve CD4 +T cells decreased in the remission group. The analysis of T cells classified according to chemokine receptors showed that memory (29.1±4.0 vs 22.7±2.7 × 10 4  cells/mL; p=0.06) and naïve (22.6±4.1 vs 17.2±2.8; p=0.04) CD4 +with CXCR3 +and with CCR4 +were the subsets that decreased significantly in the remission group but not in the non-remission group. Since the expression of chemokine receptors defines the different Th subpopulations, we analysed them in the two groups of patients. Th1 tended to decreased in the remission group (3.5±0.7 vs 2.5±0.4; p=0.06) and Th9 decreased significantly in both groups (R: 5.0±0.8 vs 2.5±0.3; p=0.006 and Non R 5.5±0.8 vs 3.1±0.4; p=0.001). In regard to the cytokines produced by CD4 +T lymphocytes, IL-17 (2.1±1.1 vs 1.2±0.5 ng/ml; p=0.04) and VEGF (0.5±0.2 vs 0.3±0.1 ng/ml; p=0.05) but not IL-6 and IL-22 changed significantly in the remission group. Interestingly, IL-17 and VEGF correlated with US findings before the initiation of the treatment (grey scale R=0.378, p=0.01 and R=0.322, p=0.03; power Doppler R=0.415, p=0.004 and R=0.320, p=0.03 respectively). Conclusions: Tocilizumab induced changes in specific subsets of CD4 +T cells and their inflammatory associated cytokines in the remission group. Disclosure of Interest: None declared